Pengaruh Penyampaian Instruksi, Perencanaan Pembelajaran, dan Pengetahuan yang Profesional dengan Mediasi Kepuasan akan Karir terhadap Kinerja Dosen - Ignatius Jeffrey; Siddiq Waluyo (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2017)
Abstract This study aims to determine the effect of the delivery of instruction, learning planning, and professional knowledge with mediation of career satisfaction on the performance of the lecturer at Muhammadiyah University Tangerang. The analysis of managerial implications is done by grouping the average value of respondent data for each variable based on demographic data: age, gender, education level, and functional position. The method used in this research was quantitative analysis technique SEM, that was used to determine the effect of instruction delivery variable (X1), learning plan variable (X2), and professional knowledge (X3) with the mediation variable of career satisfaction (Y) on lecturer performance (Z). Data analysis used SEM with the overall test (F-test). The results showed there was positive and significant influence of delivery of instructions variable toward career satisfaction and there was also positive and significant influence of career satisfaction variable to the performance of lecturers.